Teachers' personal epistemologies : evolving models for informing practice - Brye, Michelle Vander Veldt; Schraw, Gregory J.; Brownlee, Jo; Olafson, Lori, 1961- (Current perspectives on cognition, learning, and instruction., 2017)
"The focus of this book is to explore teachers' evolving personal epistemologies, or the beliefs we hold about the origin and development of knowledge in the context of teaching. The chapters focus on a range of conceptual frameworks about how university and field-based experiences influence the connections between teachers' personal epistemologies and teaching practice. In an earlier volume we investigated ways in which we might change preservice teachers' beliefs and teaching practice (Brownlee, Schraw and Berthelsen, 2011). While we addressed the nature of teachers' personal epistemology, learning and teaching practices, and approaches for changing beliefs throughout teacher education programs, the volume did not address conceptual frameworks for the development of teacher's personal epistemologies. The book is focused on teacher educators, teachers and teacher education programmers in universities with an overall aim of highlighting how we might support students to engage in learning that is challenging and to engage in professional experiences that promote changes in teaching practice. We argue that students need to be encouraged to question their beliefs and develop increasingly sophisticated beliefs about their knowledge and their students' knowledge that facilitate learning and intellectual growth"--